Fault Geometry and Slip Distribution of the 2013 Mw 7.7 Balochistan Earthquake From Inversions of SAR and Optical Data. Issue 7 (3rd July 2020) - Lauer, B.; Grandin, R.; Klinger, Y.
Abstract: The 2013 Mw 7.7 Balochistan earthquake ruptured the Hoshab fault (Pakistan) over 200 km. It was dominated by left‐lateral slip, with a secondary reverse component. By combining optical (SPOT 5 and Landsat 8) and radar satellite data (RADARSAT‐2 and TerraSAR‐X ScanSAR), we derive the 3‐D coseismic displacement field and the slip distribution. Our modeling strategy involves two successive inversions allowing to explore first the fault geometry and then slip distribution. Following a statistical analysis of the coseismic surface trace, the fault is discretized into 16 segments. To determine the dip angle and down‐dip width of the segments, we then perform a non‐linear elastic inversion of the geodetic data set. Using output of this model, we prescribe the fault geometry and linearly invert for slip at depth with refined discretization. Results show a decrease of the fault dip, reaching 50° in the central part of the fault that structurally connects the two sub‐vertical terminations dipping at >70°. The distribution of strike‐slip forms a shallow continuous patch (0–8 km) that peaks at 12.7 m of slip near the epicenter. Reverse slip is distributed on several patches and becomes shallower near the southern termination, where it peaks at 5.7 m. Our model shows an absence of shallow slip deficit (SSD), as for other Mw 7.5 + strike‐slip earthquakes elsewhere, hence suggesting that SSD is only found for lesser magnitude earthquakes. We speculate that moment magnitude is a key element in the occurrence of SSD. Key Points: The combination of radar and optical satellite data constrain fault geometry and slip distribution inversions Our modeling strategy combines a non‐linear and a linear inversion that allow for modeling both the geometry and the slip distribution The large magnitude of the 2013 Mw 7.7 Balochistan earthquake explains the absence of shallow slip deficit for this earthquake